Preventing Cyberbullying in Nigeria: The Effectiveness of Social Media Literacy Education for Young People - Akeusola, Bolanle (Journal of Current Social and Political Issues, 2024)
The widespread integration of technology into daily life has transformed human interactions, creating unprecedented opportunities for creativity, collaboration, and communication. However, this digital evolution has also exacerbated cyberbullying, which poses significant threats to global and individual well-being. Cyberbullying is particularly prevalent among teenagers, who are active users of digital platforms and highly vulnerable to its negative impacts. In Nigeria, rapid technological advancements have heightened the incidence of cyberbullying, severely affecting the mental health, social development, and overall well-being of young people. This study aims to assess the effectiveness of social media literacy programs in reducing cyberbullying among Nigerian youth and examine how sociocultural and technological factors influence these interventions. Employing a quantitative cross-sectional design, data were collected from 480 students across three tertiary institutions in Lagos State using validated questionnaires. The findings revealed that social media literacy programs significantly reduced cyberbullying incidents. This study underscores the need for culturally sensitive and contextually appropriate interventions and highlights the importance of comprehensive strategies that address Nigeria's unique sociocultural and technological landscapes. Recommendations include the development of robust, evidence-based social media literacy programs tailored to diverse Nigerian communities, enhanced collaboration among stakeholders, and ongoing evaluations to refine and sustain these initiatives.